ANALISIS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN PENANGGULANGAN KEMISKINAN BERDASARKAN KERANGKA GLOBAL REPORTING INITIATIVE - ARIES JONATHAN (Media Bisnis, 2014)
Based on Government Rule No. 40 Tahun 2007 about Corporation says that a company has to make annual report about social and environment responsibility activity. Movement about CSR increase rapidly and make United Millennium Declaration to produce Millennium Development Goals with agreement priority is eliminate poverty and famine. Poverty is not only government duty but also a company duty that realize in CSR activity. CSR activity achievement by a company must be reported yearly in company social responsibility report. Company used in this thesis is Danamon Peduli Foundation. Danamon Peduli Foundation is a foundation that support community-driven development and projects that are sustainable and emphasize volunteerism. Program Activity of Danamon Peduli Foundation are My Clean, Healthy, and Prosperous Market; Relief, Recovery, Rebuild (3R); Scholarship; Program Development include is Danamon Go Green, etc. Programs Activity that operate by Danamon Peduli Foundation can be poverty alliviation programs and have impact to social community changes in their personality such as independency, competitive capability, leadership, fell of confidence, and decrease in consumptive lifestyle. Therefore, programs have impact to related government institution and DSP units. Activities that operate by Danamon Peduli Foundatioan have been disclosed based on mandatory criteria and have been completed by voluntary criteria. From analysis and discussion has conclusion that programs activity by Danamon Peduli Foundation are poverty alliviation program such as scholarship, Danamon Go Green that can create work force for new work field. Programs effectivity is reliable because the beneficiary can feel directly the impact and the contribution of the programs.